2001
DOI: 10.1093/nar/29.4.886
|View full text |Cite
|
Sign up to set email alerts
|

Splicing of constitutive upstream introns is essential for the recognition of intra-exonic suboptimal splice sites in the thrombopoietin gene

Abstract: The human thrombopoietin (TPO) gene, which codes for the principal cytokine involved in platelet maturation, shows a peculiar alternative splicing of its last exon, where an intra-exonic 116 nt alternative intron is spliced out in a fraction of its mRNA. To characterize the molecular mechanism underlying this alternative splicing, minigenes of TPO genomic constructs with variable exon-intron configurations or carrying exclusively the TPO cDNA were generated and transiently transfected in the Hep3B cell line. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 43 publications
6
17
0
Order By: Relevance
“…This finding underlines the importance of the acceptor site in splice site selection. This is in agreement with a recent study [22] in which it was shown that mutating the acceptor site to a stronger site was more effective for full intron splicing of an alternative intron, than strengthening the donor site. Likewise, there was an inverse relationship found between the length of the polythimidine tract, which influences the acceptor strength, at the exon 9 acceptor site and the proportion of exon 9 deleted CFTR mRNA transcripts [23].…”
Section: Resultssupporting
confidence: 93%
“…This finding underlines the importance of the acceptor site in splice site selection. This is in agreement with a recent study [22] in which it was shown that mutating the acceptor site to a stronger site was more effective for full intron splicing of an alternative intron, than strengthening the donor site. Likewise, there was an inverse relationship found between the length of the polythimidine tract, which influences the acceptor strength, at the exon 9 acceptor site and the proportion of exon 9 deleted CFTR mRNA transcripts [23].…”
Section: Resultssupporting
confidence: 93%
“…In genes in which multiple alternative exons exist, coordination of splicing events favors some specific combinations over others. Although in many cases alternative splicing events are supposed to occur independently, some specific cases of coordination have been reported www.annualreviews.org • Regulation of Alternative Splicing (62)(63)(64), and a statistical analysis of ESTs (expressed sequence tags) suggests that it might be more common than generally thought (63). Coordination could also arise in posttranscriptional splicing if, for example, different events are regulated by a shared set of splicing factors.…”
Section: Functional Implications Of Couplingmentioning
confidence: 99%
“…In vivo cooperation between introns for their processing has been previously observed, but the mechanism has remained unclear (Neel et al 1993;Nesic and Maquat 1994;Romano et al 2001). For instance, introns of the tumor necrosis factor b (TNFb) transcript are spliced more efficiently in HeLa cells when upstream introns are still present (Neel et al 1993).…”
Section: A Novel Function For the Pre-ejc And Splicing Factor Rnps1mentioning
confidence: 99%